2015
DOI: 10.1155/2015/294197
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Correlation between Tomographic and Biomechanical Severity of Keratoconic Corneas

Abstract: Purpose. To evaluate correlation between tomographic gradation of keratoconus (KC) and its corresponding air-puff induced biomechanical response. Methods. Corneal tomography and biomechanics were measured with Scheimpflug imaging in 44 normal and 92 KC corneas. Deformation waveform was also analyzed with Fourier series. A custom KC severity scale was used from 1 to 3 with 3 as the most severe grade. Tomographic and biomechanical variables were assessed among the grades. Sensitivity and specificity of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
3
13
0
1
Order By: Relevance
“…This in turn indicated less resistance to CD because of biomechanical weakening of the cornea. 18 In this study, there was also a high correlation between the DA and AUDA in study corneas similar to the correlation in keratoconus corneas. 18 The corneal ultrastructure has a distinct distribution and orientation of collagen fibrils supported mechanically by an extracellular matrix.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This in turn indicated less resistance to CD because of biomechanical weakening of the cornea. 18 In this study, there was also a high correlation between the DA and AUDA in study corneas similar to the correlation in keratoconus corneas. 18 The corneal ultrastructure has a distinct distribution and orientation of collagen fibrils supported mechanically by an extracellular matrix.…”
Section: Discussionsupporting
confidence: 83%
“…18 In this study, there was also a high correlation between the DA and AUDA in study corneas similar to the correlation in keratoconus corneas. 18 The corneal ultrastructure has a distinct distribution and orientation of collagen fibrils supported mechanically by an extracellular matrix. 3 Imaging of the collagen fiber distribution revealed that there was an additional network of collagen crosslinks between the in-plane collagen lamellae.…”
Section: Discussionsupporting
confidence: 83%
“…A1T, A1L, and HCR were significantly lower in keratoconic eyes, and A1V, A2T, HCDA, A2V, and HCPD were higher in keratoconic eyes. Shetty and associates 22 tested A1T, A2T, and HCDA in two groups and reported similar results. These results show that biomechanically normal and stiffer corneas take a longer time to applanate, and the velocity of applanation is lower.…”
Section: Discussionmentioning
confidence: 61%
“…A limited number of studies have tested its measured parameters ability to distinguish between keratoconic and normal eyes. 5 , 20 , 21 , 22 , 23 In this study, CST was used to assess biomechanical properties of keratoconic and normal eyes. To reduce probable measurement error which corneal surface irregularity may induce the eyes with mild to moderate keratoconus were included.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal biomechanical strength is an another important factor to be considered in KC. 13 It is known that inflammation can actually lead to a transcriptional deregulation of the collagen genes 14 essential for maintaining tissue architecture. This might be an important contributor to the structural weakness observed in KC patient corneas.…”
mentioning
confidence: 99%